Suppressor Screen and Phenotype Analyses Revealed an Emerging Role of the Monofunctional Peroxisomal Enoyl-CoA Hydratase 2 in Compensated Cell Enlargement - Katano, Mana; Takahashi, Kazuki; Hirano, Tomonari; Kazama, Yusuke; Abe, Tomoko; Tsukaya, Hirokazu; Ferjani, Ali (Frontiers in Plant Science, 2016)
Efficient use of seed nutrient reserves is crucial for germination and establishment of plant seedlings. Mobilizing seed oil reserves in Arabidopsis involves β-oxidation, the glyoxylate cycle, and gluconeogenesis, which provide essential energy and the carbon skeletons needed to sustain seedling growth until photoautotrophy is acquired. We demonstrated that H+-PPase activity is required for gluconeogenesis. Lack of H+-PPase in fugu5 mutants increases cytosolic pyrophosphate (PPi) levels, which partially reduces sucrose synthesis de novo and inhibits cell division. In contrast, post-mitotic cell expansion in cotyledons was unusually enhanced, a phenotype called compensation. Therefore, it appears that PPi inhibits several cellular functions, including cell cycling, to trigger compensated cell enlargement (CCE). Here, we mutagenized fugu5-1 seeds with 12C6+ heavy-ion irradiation and screened mutations that restrain CCE to gain insight into the genetic pathway(s) involved in CCE. We isolated A#3-1, in which cell size was severely reduced, but cell number remained similar to that of original fugu5-1. Moreover, cell number decreased in A#3-1 single mutant (A#3-1sm), similar to that of fugu5-1, but cell size was almost equal to that of the wild type. Surprisingly, A#3-1 mutation did not affect CCE in other compensation exhibiting mutant backgrounds, such as an3-4 and fugu2-1/fas1-6. Subsequent map-based cloning combined with genome sequencing and HRM curve analysis identified enoyl-CoA hydratase 2 (ECH2) as the causal gene of A#3-1. The above phenotypes were consistently observed in the ech2-1 allele and supplying sucrose restored the morphological and cellular phenotypes in fugu5-1, ech2-1, A#3-1sm, fugu5-1ech2-1, and A#3-1; fugu5-1. Taken together, these results suggest that defects in either H+-PPase or ECH2 compromise cell proliferation due to defects in mobilizing seed storage lipids. In contrast, ECH2 alone likely promotes CCE during the post-mitotic cell expansion stage of cotyledon development, probably by converting indolebutyric acid to indole acetic acid.